2011
DOI: 10.1124/dmd.111.043067
|View full text |Cite
|
Sign up to set email alerts
|

Species Differences in Tissue Distribution and Enzyme Activities of Arylacetamide Deacetylase in Human, Rat, and Mouse

Abstract: ABSTRACT:Human arylacetamide deacetylase (AADAC) is a major esterase responsible for the hydrolysis of clinical drugs such as flutamide, phenacetin, and rifampicin. Thus, AADAC is considered to be a relevant enzyme in preclinical drug development, but there is little information about species differences with AADAC. This study investigated the species differences in the tissue distribution and enzyme activities of AADAC. In human, AADAC mRNA was highly expressed in liver and the gastrointestinal tract, followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 25 publications
1
60
1
Order By: Relevance
“…Rat liver microsomes (RLM) were prepared according to our previous study (Kobayashi et al, 2012b). The protein concentrations were determined according to the method of Bradford (1976) using g-globulin as the standard.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rat liver microsomes (RLM) were prepared according to our previous study (Kobayashi et al, 2012b). The protein concentrations were determined according to the method of Bradford (1976) using g-globulin as the standard.…”
Section: Methodsmentioning
confidence: 99%
“…SDS-PAGE and immunoblot analysis were performed according to our previous study (Kobayashi et al, 2012b). RLM (10 mg) were separated on 7.5% polyacrylamide gels and electrotransferred onto a polyvinylidene difluoride membrane (Immobilon-P; Millipore, Billerica, MA).…”
Section: Methodsmentioning
confidence: 99%
“…6A). Such species differences are not surprising because it has been previously reported that there are species differences in substrate specificity among human, rat, and mouse AADAC (Kobayashi et al, 2012b).…”
Section: Discussionmentioning
confidence: 85%
“…The prasugrel, a thienopyridine prodrug, hydrolase activity by human CES2 was also inhibited at high concentrations, although data for its hydrolysis were not fitted to a single substrate inhibition equation (Williams et al, 2008). In our previous studies (Watanabe et al, 2009;Kobayashi et al, 2012), the flutamide hydrolase activity in HLM was fitted to the Michaelis-Menten equation, and the EadieHofstee plot was not obviously biphasic. Therefore, we mistakenly believed that AADAC was the major enzyme responsible for flutamide hydrolysis.…”
Section: Resultsmentioning
confidence: 93%